Pterostilbene mitigates experimental pulmonary arterial hypertension by inhibiting endothelial-to-mesenchymal transition - Wang, Jie; Zhang, Yu; Liu, Junjun; Jiang, Fan; Cui, Xiaopei; Lu, Weida (Frontiers in Pharmacology, 2025)
BackgroundThe natural compound pterostilbene (PTE) has multiple cardiovascular protective effects. However, its effects on pulmonary arterial hypertension (PAH)-associated vascular remodeling remain to be elucidated. This study investigated the effects of PTE on monocrotaline (MCT)-induced PAH in rats in vivo and explored the underlying molecular mechanisms in human primary pulmonary arterial endothelial cells (hPAECs) in vitro.MethodsExperimental PAH was established by subcutaneous injection of MCT (50 mg/kg) in Sprague-Dawley rats, which were then randomly divided into vehicle or PTE (15 mg/kg via gavage) treatment groups. Endothelial-to-mesenchymal transition (EndMT) was modeled in hPAECs by treating with transforming growth factor-β, tumor necrosis factor-α, and interleukin-1β in combination.ResultsIn rats with MCT-induced PAH, administration of PTE resulted in a reduction in right ventricular systolic pressure, thereby alleviating right ventricular hypertrophy. This was accompanied by mitigation of the remodeling of pulmonary arteries. In vitro, genome-wide mRNA sequencing identified that PTE significantly downregulated the expression of high mobility group AT-hook 2 (HMGA2), a transcription factor involved in the pathogenesis of EndMT. Further, we demonstrated that PTE attenuated EndMT-related changes, including (1) reduced expression of the endothelial cell-specific markers platelet and endothelial cell adhesion molecule 1, and von Willebrand factor; (2) reduced nitric oxide production; and (3) increased expression of smooth muscle α-actin and other pro-fibrotic genes. Finally, we confirmed in vivo that PTE treatment reduced the expression of HMGA1/2 and Snai1/2 (markers of EndMT), and restored the expression of von Willebrand factor in the lungs of PAH rats.ConclusionPTE mitigates MCT-induced PAH and vascular remodeling in rats, at least in part, by inhibiting HMGA-mediated EndMT, suggesting that PTE may be a useful complementary medicine in the treatment of PAH.